Pengaruh Pelatihan Dan Disiplin Kerja Terhadap Kinerja Relawan Kantor Badan Penanggulangan Bencana Daerah Kabupaten Ogan Komering Ulu - Darman Syafe’i (LPPM Universitas Multi Data Palembang, 2021)
This study was to determine the influence of training and work discipline on the performance of volunteers at Regional Disaster Management Agency Office of Ogan Komering Ulu District. The analytical tool used is multiple regression. The results of this study are that simultaneously there is a significant influence between training and work discipline on the performance of volunteers at Regional Disaster Management Agency Office of Ogan Komering Ulu District. Partially the training variable (X1) influences the performance and work discipline (X2) influences the performance. The percentage of the influence of training and work discipline on the performance of volunteers in the Regional Disaster Management Agency Office of Ogan Komering Ulu District was 72.3% while the remaining 27.7% was influenced or explained by other variables which are not included in this research model such as work motivation, work environment and leadership (Kasmir, 2016: 189)